Efficacy and Safety of Tranexamic Acid in Pediatric Patients Undergoing Cardiac Surgery: A Single-Center Experience - Zhang, Yu; Zhang, Xue; Wang, Yang; Shi, Jia; Yuan, Su; Duan, Fujian; Wang, Yuefu; Zhang, Zhe; Jia, Yuan; Gong, Junsong; Li, Lihuan; Yan, Fuxia (Frontiers in Pediatrics, 2019)
Aims: This study evaluated the efficacy and safety of tranexamic acid (TXA) undergoing cardiac surgery. Methods: Using a retrospective cohort study design, 2,026 consecutive pediatric patients who underwent surgical repair of atrial or ventricular septal defect or complete repair of Tetralogy of Fallot were included, and divided into a control group and a TXA group. Results: Compared with that in the control group, there were statistically significant reduction of both the 12-h and total postoperative blood loss in the TXA group [6.573 ± 0.144 vs. 5.499 ± 0.133 ml kg−1, mean difference (MD) 1.074 ml kg−1, p < 0.001; 12.183 ± 0.298 vs. 9.973 ± 0.276 ml kg−1, MD, 2.210 ml kg−1, p < 0.001]. There was a statistically significant reduction of the MD of 12-h postoperative blood loss due to TXA in patients aged < 1 year compared with that in patients aged ≥1 year (MD, 1.544 vs. 0.681 ml kg-1, P = 0.007). There were statistically significant reduction of the MD of both the 12-h and total postoperative blood loss due to TXA in patients weighing < 10 kg compared with that in patients weighing ≥10 kg (MD, 1.542 vs. 0.456 ml kg-1, P < 0.001, and MD, 2.195 vs. 0.929 ml kg-1, P = 0.036, respectively). There was a statistically significant reduction of the MD of total postoperative blood loss due to TXA in cyanotic patients compared with that in acyanotic patients (MD, 3.381 vs. 1.038 ml kg−1, P = 0.002). There was no significant difference in the postoperative volume or exposure of allogeneic transfusion, in-hospital morbidity or mortality between the groups. Conclusions: TXA took effects in reduction of postoperative blood loss but not the allogeneic transfusion requirement in pediatric patients undergoing cardiac surgery, particularly in infants weighing < 10 kg and cyanotic children. Moreover, the study suggested the use of TXA was safe in pediatric cardiac surgery.